Effectiveness of a HealthMessages Peer-to-Peer Program for People With Intellectual and Developmental Disabilities - Marks, Beth; Sisirak, Jasmina; Magallanes, Rubia; Krok, Kristin; Donohue-Chase, Dina (Intellectual and developmental disabilities, 2019)
Effective strategies to improve health education, food choices, and physical activity are vital for people with intellectual and developmental disabilities (IDD), as their sedentary lifestyles and high fat diets are contributing to poor health, such as cardiovascular disease, osteoporosis, hypertension, Type II diabetes, and obesity. This study examined the effectiveness of a peer-led health promotion program for people with IDD. One group pre/post-test design was used to test the feasibility and effectiveness of the 12-week "HealthMessages Program" for three groups: peer health coaches (PHCs), mentors, and peer participants. A total of 379 volunteers participated including PHCs people with IDD (n = 33), mentors-staff from community organizations (n = 35), and peer participants-peers with IDD (n = 311). Following the intervention and 12-week "HealthMessages Program," PHCs had significant changes in physical activity and hydration knowledge, mentors had significant changes in self-efficacy scores, and peer participants had significant changes in physical activity and hydration knowledge, social supports, and total health behaviors. A dyad approach supported PHCs and mentors to implement a successful "HealthMessages Program" with their peers.